Students’ Motivation to Learn Science and Its Relationship to Their Achievement in Science: A Study in the Context of Mizoram - Kaur, Nitu; Vadhera, R.P. (SCHOOL SCIENCE, 2020)
There is a strong need for science-motivated high school students to enter the post-secondary science stream. Student enrolment in higher education science needs to be increased and higher levels of science motivation at the secondary and post-secondary levels can help to achieve this. To enrol students in various science courses, we must understand what motivates them. The purpose of the present study was to determine how secondary school students conceptualised their motivation to learn science using the Science Motivation Questionnaire (SMQ II) as a survey instrument. The students’ achievement in science courses was measured through their term-end board results of Class X. Stratified random sampling with school types as strata were used to collect the sample comprising 1134 (532 boys and 602 girls) secondary school-going children of Aizawl district of Mizoram, India. All the students studied in schools affiliated to the Mizoram Board of School Education (MBSE). Descriptive, correlation and differential analysis was used to analyse the data. The findings of the study revealed that students were found to have more than moderate level of science motivation, and the mean science achievement score of the highly motivated group was found to be maximum indicating a favourable trait of science motivation within the students. Career motivation and grade motivation were found to be the strong motivational constructs by most of the students, whereas students were least motivated by the self-determination construct. Thus, in the present population, extrinsic motivational constructs are more decisive than intrinsic ones. It was also found that there is a significant positive relationship between students’ science motivation and their achievement in science. Through differential analysis, it was revealed that a significant difference exists in the science motivation level of the high and low science achievers on all its five sub-constructs, with high achievers being more science motivated. Also, a significant difference exists in science motivational level in relation to gender, with boys being more science motivated; although, girls had a higher mean motivation level for grade motivation. However, no significant difference exists within the high and low achieving groups with regard to gender. Findings suggest that science motivation within secondary students can positively contribute to their achievement in science both at present and for their choice of a future career in science. The highlight of the findings was incorporating more of students’ positive affective traits such as, science motivation inside science classrooms.